USULAN STRATEGI BERSAING PERUSAHAAN KONTRAKTOR GOLONGAN KECIL [PROPOSED COMPETITIVE STRATEGIES OF SMALL CONTRACTOR COMPANIES] - Niken Prawirakusumah; Maria Merry Marianti (DeReMa (Development Research of Management): Jurnal Manajemen, 2022)
The construction industry is one such sector that is quite promising with regards to governmental support in this area. The needs of the Indonesian State regarding development are one of the key factors for the improvement of this sector. The construction industry consists of several groups; the small groups are often the target of competitive businesses within the industry, which often creates a negative impact on their expansion and growth. This makes the government support for small construction service providers a crucial stage in enabling them to compete with larger companies; one of which is CV. IWK. This company currently relies upon, and utilizes, the owner's extensive experience within the sector and its overall quality of work. However, the company has yet to focus on its marketing and workforce to fully capitalize on its potential growth, thereby, it tends to find it difficult to meet project targets and obligations. The company needs to maximise its strengths and further its current position in the sector by employing an appropriate strategy to implement continued penetration of the market via internal development. This is reinforced by the results of the QSPM analysis which shows that this strategy is the best choice for the company in moving forward in such a competitive market. To succeed, the main focus for the company is to delegate labor to the marketing function.Abstrak dalam Bahasa Indonesia. Sektor konstruksi menjadi salah satu sektor yang cukup menjanjikan, dukungan pemerintah dan kebutuhan negara Indonesia mengenai pembangunan menjadi salah satu faktor menggeliatnya sektor ini. Sektor konstruksi terdiri dari beberapa golongan, golongan kecil sering menjadi sasaran dampak negatif dari kompetisi antar industri, hal ini yang menjadikan pemerintah mendukung adanya dukungan terhadap penyedia jasa konstruksi kecil salah satunya adalah CV Indobuild Wahana Karya. Perusahaan ini memiliki keunggulan pada pengalaman sang pemilik dan kualitas pekerjaan yang baik. Namun perusahaan masih belum fokus terhadap pemasaran dan tenaga kerjanya sehingga perusahaan masih cenderung sulit memenuhi target proyeknya. Perusahaan berada pada posisi Hold and Maintain sehingga strategi yang sesuai adalah dengan melakukan penetrasi pasar, pengembangan pasar, dan pengembangan produk. Hal ini diperkuat dengan hasil analisis QSPM yang menunjukan bahwa strategi tersebut menjadi strategi terbaik untuk perusahaan. Namun konsekuensi yang harus dilakukan perusahaan adalah perlu mendelegasikan tenaga kerja untuk fungsi pemasaran